FRONTIER QUALITY DIFFERENTIALS IN HYBRID HIGHER EDUCATION - Coates, Hamish; Thakur, Marian (My University, 2013)
“Research capacity has large influence on a nation's competitiveness and its economic strength. Institutions can make a significant difference in the research productivity of their faculty Indeed, research shows that institutional affiliation is an important predictor of productivity over time. What this suggests is that effective scholars thrive in a certain kind of academic "ecology." The purpose of this paper is to describe several key features of this environment and to pay special attention to what will be required to cultivate the next generation of researchers.”—
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; higher education, Kazakhstan; faculty; education reforms; research productivity